CONSUMER PERCEPTION ON SERVICE OF GRAB CAR IN MEDAN - GLORIA SIANIPAR (JURNAL ILMIAH SIMANTEK, 2020)
The research aimed to know: (2) consumer perception on service of Grab Car in Medan. The type of this research isquantitative descriptive research with survey approach. The research place Medan City. The sample of this research wereconsumers which using Grab Car on December 2019 until January 2020 period as many as 100 consumers. Data collectiontechniques used questionnaires. Validity test using product moment correlation formula, while reliability test using AlphaCronbach formula with reliability coefficient value of 0.972. Data analysis technique used quantitative descriptive analysiswith percentage.The result of the research shows that consumer perception on service of Grab Car in Medan is in very good category 31respondents (31%), good category 42 respondents (42%) and p o o r c a t e g o r y 1 8 r e s p o n d e n t s ( 1 8%) andvery poor c a t e g o r y 9 r e s p o n d e n t s (9%). So it can be concluded that the tendency of frequency of consumerperception on service Grab Car in Medan is in good category (42%).